Physical Capital Estimates for China's Provinces, 1952-2015 and Beyond - Carsten A. Holz; Sun Yue (Center for Economic Studies and ifo Institute (CESifo), 2017)
Capital estimates are widely used in economic growth and productivity studies, for profitability considerations and wealth accounting exercises. Yet the calculation of “capital” frequently receives only cursory attention, despite the challenges posed by conceptual difficulties, the complexity of calculations, and the extensive data requirements. This paper (i) calculates long-run provincial (and national) physical capital series for China, (ii) distinguishes between capital services and wealth capital stock, and (iii) applies the most recent methodology advanced by the OECD, the U.S. Bureau of Labor Statistics, and the Australian Bureau of Statistics. The complete set of data is available online and is expected to be updated on an annual basis in the future.
Keywords: E01; E22; O11; O53; 330; capital services; wealth capital stock; capital concepts